Identificação de biomarcadores na síndrome mielodisplásica e predição in silico com caracterização in vitro da farmacocinética de um novo fármaco antitumoral candidato a molécula lead - Carvalho, Guilherme Graziany Camelo de (2021)
The development chain of a new drug must start from the molecular characteristics of target related to the disease/syndrome that must be treated together with characteristics of the new drug candidate. Thus, the present study aimed to identify the proteomic profile of bone marrow in myelodysplastic syndrome (MDS) and the in silico prediction profile with in vitro pharmacokinetic characterization of 2,3,9-trimethoxypterocarpane (PT+) molecule. For proteomic evaluation of myelodysplastic syndrome, bone marrow samples were collected from patients with the syndrome. Analyzes were performed by mass spectrometry with a bottom-up approach. For the pharmacokinetic characterization of PT+, in vitro evaluations of chemical, plasma and microsomal stability were performed, as well as characterization of plasma binding proteins both in vitro and in silico. Permeability assessment was performed using PAMPA. In silico prediction studies were also performed simulating the use of PT+ in healthy and cancer populations to define the pharmacokinetic profile. In these initial studies, the main proteomic findings in the plasma of MDS patients are CEP55 for MDS samples with ringed sideroblasts and talin-1, moesin and ubiquitinin-C in MDS samples with excess blasts. In low-risk MDS bone marrow cell samples, connective function proteins and fibrinogen were identified. These characteristics were recognized in previous works where alterations in the level of neutrophil degranulation and platelet malfunction were identified and confirmed at the molecular level in the first findings of this work, by evaluating proteins expressed exclusively in low-risk or high-risk groups of MDS. We emphasize that, due to the already characterized molecular action of the compound PT+ in the cell cycle, its interaction with CEP55 or with proteins of the STAT5 pathway should be better studied in future research to validate its action. Furthermore, alterations in STAT5 pathway proteins that are related to malignant processes may also serve as future studies to assess PT+ activity as a therapeutic alternative for MDS. In the pharmacokinetic evaluation, PT+ showed characteristics that place it as a candidate for future in vivo studies, as it was stable due to not suffering a significant decrease in its concentration either by action of different pH levels or by action of plasma enzymes. PT+ was shown to have strong binding to plasma proteins by the method used, ultracentrifugation, with binding of 99.39%. PT+ was also shown to have the ability to cross the blood-brain barrier and to have a high gastrointestinal absorption rate. The in silico prediction of PT+ pharmacokinetics showed that the cancer population had a faster metabolism than the control population (caucasians). This shows PT+ with an adequate profile for in vivo validation of molecular findings for myelodysplastic syndrome. Among the main proteomic findings in the plasma of patients and given the results, it was possible to recognize that PT+ is a potential candidate for further study as a therapeutic alternative for the treatment of MDS.